Actualization of Religious Values through Religious Tourism on the River As a Source of Social Studies Learning - Ersis Warmansyah Abbas; Jumriani Jumriani; Muhammad Rezky Noor Handy; Syaharuddin Syaharuddin; Nadiatul Izmi (STAI Hubbulwathan Duri, 2021)
Quality human resources are needed to support development. To produce these resources requires a variety of attitudes. One of them is religious attitudes as a preventive measure against immoral behaviour currently rife in society. From a local perspective, religious tourism can be done to learn in realizing religious attitudes. In the city of Banjarmasin, there is a religious tour of the Habib Basirih Dome that can actualize students' religious values through various religious activities. This article explores religious tourism on the river as a learning resource to actualize students' religious values. Qualitative approach with a descriptive method is used with data collection techniques through interviews, observation, and documentation. The validity of the data is done through triangulation of sources, time, and techniques. The study results ensure that religious tourism on f the river, precisely in the Habib Basirih Dome, can be used to actualize students' religious attitudes. Therefore, teachers can use it by planning, implementing, and evaluating in the context of social studies subjects by the content of religious characters through religious tourism on the river, precisely in the Basirih Dome.